2013
DOI: 10.4321/s0213-12852013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia del segundo canal en la raíz mesiovestibular de los primeros molares maxilares mediante tomografía computarizada de haz de cono

Abstract: Prevalencia del segundo canal en la raíz mesiovestibular de los primeros molares maxilares mediante tomografía computarizada de haz de cono AVANCES EN ODONTOESTOMATOLOGÍA/ 31 RESUMEN Introducción: La morfología del sistema de canales radiculares es compleja y variable. El primer molar maxilar permanente presenta habitualmente un segundo canal en la raíz mesiobucal (MB2). Su falta de localización y total desbridamiento, es la principal causa de fracaso terapéutico. El objetivo fue determinar la prevalencia in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
(11 reference statements)
3
4
1
2
Order By: Relevance
“…These results are consistent with those reported by Fogel et al [26] and Betancourt et al [14]. However, Zheng et al [1] and Betancourt et al [12] found no difference. The smaller detection percentage of the MB2 canal in women could be explained by the demineralization and loss of bone mass in adults being three times greater in women [27], which would prevent the correct observation of the canal through computerized tomography due to lack of contrast.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with those reported by Fogel et al [26] and Betancourt et al [14]. However, Zheng et al [1] and Betancourt et al [12] found no difference. The smaller detection percentage of the MB2 canal in women could be explained by the demineralization and loss of bone mass in adults being three times greater in women [27], which would prevent the correct observation of the canal through computerized tomography due to lack of contrast.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained in this study revealed a prevalence of the MB2 canal in 69.81% in the 1MM, similar to that reported with the same diagnostic method by Kim et al (63.59%) [20], Lee et al (70.5%) [15], Betancourt et al (68.75%) [12] and higher than the 52% reported by Zhang et al [3] and the 8.78% by Zheng et al [1]. The MB2 canal in the 2MM was identified in 46.90% of the cases, a percentage similar to the results reported using CBCT by Betancourt et al (48%) [14], Lee et al (42.2%) [15], and higher than the 34.32% by Silva et al [21] and the 22% observed by Zhang et al [3].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations